The circular economy, 5R framework, and green organic practices: pillars of sustainable development and zero-waste living - Kshitij K. Meshram (Discover Environment)
Abstract The United Nations (UN) strives for critical raw materials(CRMs) via sustainable development goals(SDGs). The growing population and pollution have thrusted the demand for critical materials for progressive science and technology and stunted overall economic growth worldwide. The current linear economy relies on a take-make-dispose policy. This approach extracts, uses and depletes CRMs which leads to ecological imbalance. Waste has become a major challenge for the sustainability of planet. Concerning to achieving UN sustainable development goals, the global mandate is to replace the outdated linear economy, this change is important for addressing material criticality and it can be possible because of the pillars of SDGs (Circular economy, 5Rs’ and Green-organic domain). At the start of this millennium, the world underwent economic transition. It moved from linear-circular and brown-green. This universal movements aim for Zero-Waste living. Consequently, 5R’s concept, i.e., Rethink, Refuse, Reduce, Reuse and Recycle, is an aptly irresistible weapon for combating ever-increasing waste/pollution for sustainable growth. In this regard, green organic principles are considered to stride to a circular and green economic perspective for better use of CRMs. The pillars of SDGs prevent potential destructive impacts on the environment and human health. They promote green-organic domain practices to obtain a more sustainable economy, addition to boosting quality of life by harmonizing disturbed climate change. Graphical Abstract